The Importance of Self-Defense Competence for Aviation Security Personnel - Febiyanti, Herlina; Destyana, M Erawan; Lestari, Witri Ayu (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This study was conducted at the Palembang Aviation Polytechnic in April 2021 until October 2021. The method used in this study is descriptive. This research is descriptive in nature, namely reporting observations on phenomena in the field or social. Data collection techniques using questions in the form of a questionnaire via google forms, observations made by the author, and interviews with the Aviation security training instructor at the Palembang Aviation Polytechnic. The research population is all flight security personnel throughout Indonesia by taking sample data which is the result of responses from respondents who enter after distributing Google Forms for two months since the questionnaire was distributed from April-June 2021. The result showed that self-defense is the answer to these problems because self-defense can be interpreted as internal competence to defend oneself, a group or even a country.